A rare case of Gynura-segetum-related hepatic sinus obstruction syndrome complicated with alcoholic liver disease - Yidan Gao; Xiangbo Zhang; Xiang Zhou; Jie Wang; Ling Gong; Gongying Chen (Journal of the Pakistan Medical Association)
Hepatic sinus obstruction syndrome (HSOS) is easy to be misdiagnosed or missed, and there is no unified and effective treatment for it. A patient was considered to have Budd-Chiari syndrome. He underwent a transjugular liver biopsy, and pathological examination revealed HSOS without liver cirrhosis. After the failure of anticoagulation therapy, he successfully received a transjugular intrahepatic portosystemic shunt (TIPS). After discharge, he was followed-up for four years with a good prognosis. G. segetum-induced HSOS can be easily overlooked, especially in patients with underlying liver diseases. When medical therapy fails, TIPS can control ascites and portal hypertension, and the long-term prognosis is optimistic.